Some verbal behavior about verbal behavior - Salzinger, Kurt (2003)
Beginning with behavior analysts' tendency to characterize verbal behavior as “mere” verbal behavior, the author reviews his own attempt to employ it to influence both his staff and policies of our government. He then describes its role in psychopathology, its effect on speakers in healing themselves and on engendering creativity. The paper ends by calling to our attention the role of verbal behavior in the construction of behavior analysis.